2012
DOI: 10.1042/an20110038
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neurons Derived from Diabetic Rats Have Diminished Internal Ca2+ Stores Linked to Impaired Re-uptake by the Endoplasmic Reticulum

Abstract: Distal symmetrical sensory neuropathy in diabetes involves the dying back of axons, and the pathology equates with axonal dystrophy generated under conditions of aberrant Ca2+ signalling. Previous work has described abnormalities in Ca2+ homoeostasis in sensory and dorsal horn neurons acutely isolated from diabetic rodents. We extended this work by testing the hypothesis that sensory neurons exposed to long-term Type 1 diabetes in vivo would exhibit abnormal axonal Ca2+ homoeostasis and focused on the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
(99 reference statements)
0
26
0
Order By: Relevance
“…Normal SERCA function is required to maintain intracellular stores that provide releasable Ca 2+ , which in turn regulates neuronal excitability (Gemes et al, 2011). SERCA dysfunction contributes to numerous pathological conditions, including diabetic axonopathy (Zherebitskaya et al, 2012), Ca 2+ overload during neuronal ischemia (Larsen et al, 2005; Henrich and Buckler, 2008), age-associated neuronal degeneration (Pottorf et al, 2000a,b), excitotoxicity (Fernandes et al, 2008), ER stress and apoptosis (Mengesdorf et al, 2001; Verkhratsky, 2004; Gallego-Sandin et al, 2011). Little is known about the modulation of SERCA function after peripheral nerve injury or its role in chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Normal SERCA function is required to maintain intracellular stores that provide releasable Ca 2+ , which in turn regulates neuronal excitability (Gemes et al, 2011). SERCA dysfunction contributes to numerous pathological conditions, including diabetic axonopathy (Zherebitskaya et al, 2012), Ca 2+ overload during neuronal ischemia (Larsen et al, 2005; Henrich and Buckler, 2008), age-associated neuronal degeneration (Pottorf et al, 2000a,b), excitotoxicity (Fernandes et al, 2008), ER stress and apoptosis (Mengesdorf et al, 2001; Verkhratsky, 2004; Gallego-Sandin et al, 2011). Little is known about the modulation of SERCA function after peripheral nerve injury or its role in chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Global explanation for unchanged level of α‐KG in serum and urine may be attributed to simultaneous decrease of TCA cycle intermediates and enzyme activities, including citrate (upstream of TCA cycle; the source of α‐KG synthesis) and α‐KG dehydrogenase (α‐KGDH; catalysing the α‐KG to succinyl‐CoA reaction) . Therefore, the level of α‐KG remained stable under this situation.…”
Section: Discussionmentioning
confidence: 99%
“…A significant decrease in microsomal Ca 21 levels could be attributed to altered SERCA activity that was observed. The diminished ability of the ER to accumulate Ca 21 , which could lead to an increase in resting [Ca 21 ] i , was observed in neurons from diabetic rats (Zherebitskaya et al, 2012). Furthermore, increased availability of L-VOCC leads to ryanodine receptor-mediated Ca 21induced Ca 21 release from the ER, which would further amplify L-VOCC Ca 21 transients (Toescu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in SERCA activity was found to be associated with decreased SERCA mRNA expression in the cerebral cortex and in the heart of diabetic animals (Teshima et al, ; Pottorf et al, ). Zherebitskaya et al () suggested that impairment in the mitochondrial respiratory chain in diabetes might be responsible for suboptimal ATP delivery for SERCA function, resulting in reduced SERCA activity (Chowdhury et al, ). Verkhratsky et al (2008) suggested the role of insulin in mitochondrial dysfunction, which resulted in alterations in Ca 2+ ‐ATPase activity.…”
Section: Discussionmentioning
confidence: 99%